2017
DOI: 10.1097/ccm.0000000000002327
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Probability and Time to Reintubation in U.S. ICUs

Abstract: OBJECTIVE Reintubation after liberation from mechanical ventilation is viewed as an adverse event in intensive care units (ICUs). We sought to describe the frequency of reintubations across U.S. ICUs and to propose a standard, appropriate time cut-off for reporting of reintubation events. DESIGN & SETTING We conducted a cohort study using data from the Project IMPACT database of 185 diverse ICUs in the U.S. PATIENTS We included patients who received mechanical ventilation and excluded patients who received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
2
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 32 publications
(43 reference statements)
5
26
2
5
Order By: Relevance
“…We report that 47% of infants ≤ 1,250 g and 58% of infants ≤ 1,000 g were reintubated at least once during hospitalization, a finding consistent with results of other large cohort studies (4,11). However, these reintubation rates are much higher than those reported for adult (10%) and children (6%) patients (12,13). Given the morbidities associated with reintubation and resumption of MV, clinicians and investigators alike are increasingly searching for strategies that can reduce rates of reintubation in this population (7).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We report that 47% of infants ≤ 1,250 g and 58% of infants ≤ 1,000 g were reintubated at least once during hospitalization, a finding consistent with results of other large cohort studies (4,11). However, these reintubation rates are much higher than those reported for adult (10%) and children (6%) patients (12,13). Given the morbidities associated with reintubation and resumption of MV, clinicians and investigators alike are increasingly searching for strategies that can reduce rates of reintubation in this population (7).…”
Section: Discussionsupporting
confidence: 90%
“…First, with the increased use of non-invasive ventilation following extubation, reintubation may be delayed rather than actually prevented. This phenomenon has actually been described in the adult population, whereby the increased use of non-invasive respiratory support has shifted the window of observation from the traditional 48 to 96 h postextubation (12,16). Indeed, in our cohort, although infants were extubated to continuous positive airway pressure or nasal intermittent positive pressure ventilation equally often, the majority had escalated to nasal intermittent positive pressure ventilation by the time they were reintubated.…”
Section: Discussionsupporting
confidence: 51%
“…8 Both delayed and premature extubation may be correlated to an increased risk of various complications, 31,32 and the need for reintubation or tracheostomy was viewed as a potential adverse event after CABG. [31][32][33] Previous studies found that requiring reintubation or tracheostomy was associated with organ dysfunction, especially respiratory failure, secondary to physiologic stress, increased mortality, higher hospital costs and longer length of ICU stay. [34][35][36] Among CHD patients following CABG, OSA was correlated to a longer intubation time.…”
Section: Discussionmentioning
confidence: 99%
“…A anticoagulação durante a ECMO é utilizada para prevenir complicações trombóticas, e tem sido muito estudada na tentativa de encontrar formas para aprimorar as técnicas de anticoagulação (MILTIADES et al, 2017;LO-PINTO et al, 2018). A heparina é mais frequentemente usada, e o monitoramento normalmente é feito através dos testes de tempo de coagulação ativada (TCA) e de tempo de tromboplastina parcial ativada (TTPa), de níveis de fibrinogênio, tempo de atividade da protrombina (TAP) e a contagem de plaquetas que são rotineiramente conferidos e corrigidos se necessário.…”
Section: Anticoagulação Durante a Ecmounclassified